2008
DOI: 10.1051/0004-6361:200809502
|View full text |Cite
|
Sign up to set email alerts
|

The nature and evolution of Nova Cygni 2006

Abstract: Aims. Nova Cyg 2006 has been intensively observed throughout its full outburst. We investigate the energetics and evolution of the central source and of the expanding ejecta, their chemical abundances and ionization structure, and the formation of dust. Methods. We recorded low, medium, and/or high-resolution spectra (calibrated into accurate absolute fluxes) on 39 nights, along with 2353 photometric UBVR c I c measures on 313 nights, and complemented them with IR data from the literature. Results. The nova di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 48 publications
8
91
1
Order By: Relevance
“…An increase of the observed colour index B−V from ∼0.1 to ∼0.55 between Aug. 15.0 and 19.2 (see Fig. 2 of Munari et al 2013a) corresponded to a change of the spectral type of the expanding envelope from ∼A2 to ∼F8 (cf. Cox 2000).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…An increase of the observed colour index B−V from ∼0.1 to ∼0.55 between Aug. 15.0 and 19.2 (see Fig. 2 of Munari et al 2013a) corresponded to a change of the spectral type of the expanding envelope from ∼A2 to ∼F8 (cf. Cox 2000).…”
Section: Introductionmentioning
confidence: 94%
“…Relative flux units were converted into absolute fluxes with the aid of the (near-)simultaneous BVR C I C photometry of Munari et al (2013a) and/or UBV photometry from the AAVSO database. Magnitudes were converted to fluxes according to the calibration of Henden & Kaitchuck (1982).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some novae (eg. Nova Aql 1994a, Nova Cyg 2006, Nova Cyg 2008bVenturini et al 2004, Munari et al 2008a, Munari et al 2011c, have displayed just one such event over their recorded photometric history. Strope et al (2010) in their review of AAVSO lightcurves of a hundred novae, termed J-type (from "jitter") the novae showing multiple secondary maxima.…”
Section: Photometric Evolutionmentioning
confidence: 99%
“…Pre-outburst optical photometry showed that it was varying by a few tenths of a magnitude, around ∼17.5 mag, up to about 10 d before eruption (Deacon et al 2014). Extensive broad-band optical photometry following the eruption was given by Munari et al (2013b). The visual light curve is given in Fig.…”
Section: 3 9 D E L P H I N Imentioning
confidence: 99%